2020
DOI: 10.3389/fgene.2020.00287
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Aspects of Neuronal Hyperploidization in Alzheimer’s Disease Evidenced by Computer Simulation

Abstract: When subjected to stress, terminally differentiated neurons are susceptible to reactivate the cell cycle and become hyperploid. This process is well documented in Alzheimer's disease (AD), where it may participate in the etiology of the disease. However, despite its potential importance, the effects of neuronal hyperploidy (NH) on brain function and its relationship with AD remains obscure. An important step forward in our understanding of the pathological effect of NH has been the development of transgenic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Of relevance is also the demonstration that NT is prevented by neuronal E2F4DN expression. Cell cycle reentry, together with neuroinflammation, has been proposed to be major drivers of AD ( 10 ), likely due to its capacity to induce NFTs, extracellular deposits of Aβ, gliosis, synaptic dysfunction and delayed neuronal cell death [reviewed by ( 12 )]. Furthermore, NT triggers synaptic dysfunction ( 83 ) and may affect neuronal structure and function ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of relevance is also the demonstration that NT is prevented by neuronal E2F4DN expression. Cell cycle reentry, together with neuroinflammation, has been proposed to be major drivers of AD ( 10 ), likely due to its capacity to induce NFTs, extracellular deposits of Aβ, gliosis, synaptic dysfunction and delayed neuronal cell death [reviewed by ( 12 )]. Furthermore, NT triggers synaptic dysfunction ( 83 ) and may affect neuronal structure and function ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle reentry, together with neuroinflammation, has been proposed to be major drivers of AD ( 10 ), likely due to its capacity to induce NFTs, extracellular deposits of Aβ, gliosis, synaptic dysfunction and delayed neuronal cell death [reviewed by ( 12 )]. Furthermore, NT triggers synaptic dysfunction ( 83 ) and may affect neuronal structure and function ( 12 ). Our results are consistent with the observation that prevention of NT in the cerebral cortex of aged E2f1 -/- mice correlates with enhanced cognition ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…that immediately followed and were truncated by DOWN states. DOWN-state responses were aligned by the delta peak or the end of the DOWN epoch (DOWN-UP transition), as indicated.Spiking network simulations.We built a network model of leaky integrate-and-fire neurons based in Jercog et al15 , and Barrio et al51 , using the Python-based simulator Brian2 52 . We include n PYR = 4000 excitatory, n INT = 1000 inhibitory and n DSA = 100 neurons with the following connection probability (c): c PYR-PYR = 0.1, c PYR-INT = 0.1, c INT-INT = 0.2, c INT-PYR = 0.3, c PYR-DSA = 931 0.05, c INT-DSA = 0.3, c DSA-PYR = 0.1 and c DSA-INT = 0.1.…”
mentioning
confidence: 99%
“…Various indicators of cell cycle arrest such as cell cycle inhibition and telomere attrition have been discussed for mitotically competent brain cells, for example [ 18 ]. Despite the persistent dogma that neurons permanently withdraw from the cell cycle upon terminal differentiation, numerous studies have demonstrated the expression of cell cycle proteins in post-mitotic neurons, that can give rise to dysfunctional hyperploid cells [ 19 ]. A decrease in telomere length is associated with cell division; notably telomere shortening has been observed in non-replicative neural brain populations in C57BL/6 mice in a cell cycle-independent manner [ 20 ].…”
Section: Identifying Senescent Brain Cellsmentioning
confidence: 99%